Fabulous4u : product development process for a brand new islamic nursing attire - Lailatul Asmah Mohd Tahir (2014)
This case is pertaining to new start-up company, Fabulous Mom and Baby Boutique which is operated as a one stop center for mother and baby’s products. As a new start-up company, this boutique concern about the process of developing new product which is focusing on nursing attire for lactating mother. This case is an exploratory multiple methods from the previous research to analysis of new product development process normally practiced in the apparel industry. The process, which is consider the customers’ needs and satisfaction as a center of the product development process from the aspect of functional needs (lactating process) and aesthetics needs (Islamic concept).